PELAKSANAAN PEMBAGIAN WARISAN PADA MASYARAKAT TIONGHOA DI GUNUNGSITOLI-NIAS (STUDI PADA: PERSATUAN AMAL SOSIAL GUNUNGSITOLI-NIAS) - CINDY CINDY (PREMISE LAW JURNAL, 2016)
The implementation of distributing inheritance in the Chinese of the Indonesian citizens is based on the Civil Code since there is no law which regulates it. The implementation of distributing inheritance in the Chinese community in Gunungsitoli, Nias is based on the Chinese adat law by discussing the share of each heir in a spirit of mutual cooperation and consensus. The legal consequence of this system is that it is binding for the heirs to comply with it. It becomes the basic philosophy for settling any conflict about the distribution of inheritance so that it is the least possibility for the heirs not to agree with this amicable decision because of the strong adat tradition among the Chinese community, and the adat law practitipners themselves have admitted its existence. Keywords: Inheritance, Chinese Community